A select library of the Nicene and Post-Nicene Fathers of the Christian church - Chrysostom, Saint; Schaff, Philip, 1819-1893 (Edinburgh, Scotland T and T Clark, 1889)
Contents: vol. IX : Saint Chrysostom / On the priesthood; Ascetic treatises; Select homilies and letters; Homilies on the statues. Includes indexes.
Keywords: Fathers of the church -- Primitive and early church -- ca 30-600.; Chrysostom, Saint